Optimized design of permanent magnet brushless DC motor for ceiling fan applications. (2021) - Bhuvaneswari, S.; Sivaraman, P.; Anitha, N.; Matheswaran, A.
Abstract: The objective of this research to design a compact electrical motor for a ceiling fan to save more electric power. Presently, single phase induction motor is used for ceiling fan application. Losses generated by single phase induction are more and hence efficiency is lower. In addition, overload is not handled by single phase induction motor whereas DC models can handle a lot of overload quite easily. In induction motor, the rotor frequency is lesser than stator frequency i.e rotor frequency is slip times the stator frequency. AC induction motor uses capacitor in anyone of its phases to excite and rotate the machine, so it is larger in size. In this paper, the axial flux type of permanent magnet machine configuration is selected to propose the optimum design of ceiling fan machine. The proposed configuration has single stator and single rotor for the axial flux permanent magnet Brushless Direct current Motor (BLDC) machine. By using the magnet software, the analysis of proposed machine has been done in terms of various aspects such as the induced voltage, phase current and air gap flux density.